Mapping the farms surrounding the town of Csongrád (Academic Journal of Internal Affairs, 2024)
The authors provide an overview of the process of building a computerised information map database system based on photos of the extensive farm network around Csongrád town, established with the help of the local neighbourhood watch organisations.
Keywords: Csongrád; farmhouse; database